Effect of Vitamin D Deficiency on the Occurrence and Recurrence of Benign Paroxysmal Positional Vertigo: A Narrative Review - Raid Al-Ani; Taghreed Al-Rawi; Ahmad Aljuboori; Harith Ahmed (University of Kirkuk, College of Medicine, Kirkuk, Iraq, 2024)
Benign paroxysmal positional vertigo (BPPV) is a short-lived attack of rotatory vertigo provoked by certain head movements. The most acceptable theories for its pathogenesis are canalithiasis and cupulolithiasis as a result of the detachment of otoconia from the otolithic membrane. Although canal repositioning maneuvers resolve BPPV, recurrence is a common feature. During the last two decades, there is a revolution in research in understanding many aspects of thisdisorder. The advanced age, female gender, migraine, Meniere’s disease, trauma, and infection are recognized examples of the BPPV causes. Vitamin D deficiency or insufficiency is considered a risk factor for the occurrence and recurrence of the disease as indicated by many investigations. Therefore, estimation of vitamin D serum level in all subjects with BPPV is highly recommended. In addition to canal repositioning procedures such as the Epley maneuver, vitamin Dsupplementation in patients with deficient or insufficient vitamin D is the best treatment for primary BPPV. In this review, we discussed the updating knowledge of the risk factors of BPPV as an initiator for the disease or a risk factor forits recurrence.